2007
DOI: 10.1002/anie.200605019
|View full text |Cite
|
Sign up to set email alerts
|

Reverse Micelles in Carbon Dioxide with Ionic‐Liquid Domains

Abstract: The fluorinated surfactant N‐ethyl perfluorooctylsulfonamide can form reverse micelles with an ionic liquid as the inner component in supercritical CO2. These reverse micelles can solubilize salts and gold nanoparticles can be formed with HAuCl4 (see TEM image). The micellar systems may combine some of the advantages of supercritical CO2 and ionic liquids as solvents with benefits for potential applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
91
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(96 citation statements)
references
References 46 publications
4
91
1
Order By: Relevance
“…11 Recently, Han and his co-workers discovered that the 1,1,3,3-tetramethylguanidinium type of ILs can be dissolved in supercritical CO 2 reverse micelles. 27 They also reported that 1-butyl-3-methylimidazolium hexafluorophosphate ([bmim] [PF 6 ]) can be dispersed in propylammonium formate (PAF), another type of IL. 28 Smallangle neutron scattering (SANS) was used to investigate the [bmim] [BF 4 ]/Triton X-100/cyclohexane microemulsion, and a swelling behavior consistent with water-in-oil (W/O) microemulsions was observed.…”
Section: Introductionmentioning
confidence: 99%
“…11 Recently, Han and his co-workers discovered that the 1,1,3,3-tetramethylguanidinium type of ILs can be dissolved in supercritical CO 2 reverse micelles. 27 They also reported that 1-butyl-3-methylimidazolium hexafluorophosphate ([bmim] [PF 6 ]) can be dispersed in propylammonium formate (PAF), another type of IL. 28 Smallangle neutron scattering (SANS) was used to investigate the [bmim] [BF 4 ]/Triton X-100/cyclohexane microemulsion, and a swelling behavior consistent with water-in-oil (W/O) microemulsions was observed.…”
Section: Introductionmentioning
confidence: 99%
“…This kind of microemulsions may have potential applications with some advantages due to the water-free and nonvolatile natures. Very recently, they also discovered that N-ethyl perfluorooctylsulfonamide (C 2 H 5 NHSO 2 C 8 F 17 ; N-EtFOSA) can form reverse microemulsions in supercritical CO 2 with 1,1,3,3-tetramethylguanidinium ([(CH 3 ) 2 N] 2 C=NH 2 + ) acetate (TMGA), 1,1,3,3-tetramethylguanidinium lactate (TMGL), and 1,1,3,3-tetramethylguanidinium trifluoroacetate (TMGT) domains [53]. The combination of supercritical CO 2 and ILs is interesting from academic, environmental and practical points of view as the systems may combine some advantages of the two fluids.…”
Section: Self-assembled Microemulsions In Ilsmentioning
confidence: 99%
“…The surfactant N-ethyl perfluorooctylsulfonamide (N-EtFOSA) forms microemulsions in a solvent mixture of the IL 1,1,3,3-tetramethylguanidinium acetate (TMGA) and SCCO 2 , as the interactions between CO 2 and the fluorocarbon tails of the surfactants are strong. 53,54 In a standard synthesis procedure, Zn(NO 3 ) 2 , 1,4-benzenedicarboxylic acid (H 2 bdc) and N-EtFOSA were added to TMGA and heated in a high-pressure cell under 16.8 MPa CO 2 pressure at 80 C for 48 h. Transmission electron microscopy (TEM) images (Fig. 2) show nanoparticles of roughly 80 nm diameter with a uniform size distribution and a well ordered system of mesopores.…”
Section: Microemulsion Synthesismentioning
confidence: 99%